THE LANGUAGE OF IMAGERY AS A COMPONENT OF THE PROFESSIONAL TRAINING OF FUTURE MATHEMATICS TEACHERS - Losyeva, Nataliya; Horoshko, Oleksandr (My University, 2026)
The article examines the concept of the «language of images» as an element of mathematical education, for the perception of abstract mathematical concepts in a visual format, facilitating their assimilation and understanding. The language of images is expressed through its syntax, semantics and pragmatics, as a basis for the formation of the visual subcompetence of the mathematics teacher as a component of information competence. The research addresses retrospective aspects of the use of visual aids in teaching mathematics, describes modern digital tools, their role in the development of critical thinking and their role in the development of the language of images in mathematics education. Special attention is also paid to the strategy of forming future teachers’ visual subcompetence as an important component of their information competence, which is based on analysis, creation and interpretation of visual models. Recommendations for the integration of the language of images into pedagogical practice are proposed in order to increase the effectiveness of mathematics education.
Keywords: visualization; visual subcompetence; mathematics education; language of images; teacher professional training; digital instruments